2009
DOI: 10.1107/s1600536809053458
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-1-(3-Chlorophenyl)-3-phenylprop-2-en-1-one

Abstract: In the title compound, C15H11ClO, the dihedral angle between the mean planes of the benzene ring and the chloro-substituted benzene ring is 48.8 (3)°. The dihedral angles between the mean plane of the prop-2-ene-1-one group and the mean planes of the 3-chloro­phenyl and benzene rings are 27.0 (4) and 27.9 (3)°, respectively. In the crystal, weak inter­molecular C—H⋯π-ring inter­actions occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…(2 E )‐1,3‐Bis(4‐chlorophenyl)‐2‐propen‐1‐one ( 1 ) was synthesized by the Claisen–Schmidt condensation method 28, which was performed with hydrogen peroxide in alkaline medium to produce (4‐chlorophenyl)[3‐(4‐chlorophenyl)oxiranyl] methanone ( 2 ) (Scheme ). Analytical and spectral data of compound 2 are in agreement with the proposed structure (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2 E )‐1,3‐Bis(4‐chlorophenyl)‐2‐propen‐1‐one ( 1 ) was synthesized by the Claisen–Schmidt condensation method 28, which was performed with hydrogen peroxide in alkaline medium to produce (4‐chlorophenyl)[3‐(4‐chlorophenyl)oxiranyl] methanone ( 2 ) (Scheme ). Analytical and spectral data of compound 2 are in agreement with the proposed structure (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Follow up of the reactions and checking the purity of the compounds was made by TLC on silica gel‐precoated aluminum sheets (Type 60 F254; Merck, Darmstadt, Germany). Compound 1 was prepared according to a reported method 28.…”
Section: Methodsmentioning
confidence: 99%
“…The white precipitate was filtered off and dried under vacuum over anhydrous CaCl 2 . The light yellow, white and light green of [Fe(L) 2 4 .6H 2 O were prepared in similar manner described above by using acetone as a solvent and using Fe(NO 3 ) 3 .9H 2 O, CoCl 2 .6H 2 O and NiSO 4 .8H 2 O, respectively, in 1:2 molar ratio.…”
Section: Preparation Of the Metal Complexesmentioning
confidence: 99%
“…However, this procedure is time consuming and gives low yield. Jasinski et al [2,3] had reported an easy one-step synthesis which gives a higher yield of ligand by heating a mixture of 4-chloroacetophenone, 4-chlorobenzaldehyde, ethyl cyanoacetate and ammonium acetate in presence of glacial acetic acid as a catalyst.…”
Section: Introductionmentioning
confidence: 99%